The Coast of Teeth and Eyes: Drawing the seaside from the inside out: Drawing the seaside from the inside out - Netter, Louis Richard (BBDS - Black Book: Drawing and Sketching, 2021)
The ongoing research/book project provisionally titled A Coast of Teeth, is an exploration of English seaside towns through drawing and writing. My own role as a reportage artist is to respond to what I see and document it in-situ. What we have found on our travels to Torquay, Paignton, Bournemouth, Clacton-on-Sea, Jaywick and Weston Super Mare are landscapes which are reflective of the socio-economic realities on the ground and a people who bare the physio-psycho trauma of such conditions in their behaviours and physicality. Internal conflict manifests itself in physical conditions such as obvious physical disability, anti-social behaviour, obesity and malnutrition from drug use. Working with a writer, it is interesting to see how the writing and the drawing speaks to internal and external realities and the convergence of past and present as an evolving circumstance for people in these towns who struggle for relevance and economic sustenance. Drawings evolve from the same process as all vision and understanding; a refined cataloguing of people, places and things. This piece explores how drawings can capture momentary insights that elude writing and approximate the complex convergence of vision, thought and experience.